Anovestibular fistula with normal anal opening: Is it always congenital? - Jain Prashant; Mishra Pankaj; Shah Hemanshi; Parelkar Sandesh; Borwankar S (Wolters Kluwer Medknow Publications, 2008)
Aim: To review 12 cases of anovestibular fistula with normal anal opening. Methods: Retrospective analysis of 12 children with anovestibular fistula and normal anal opening were treated between the years 2000 and 2007. Of these, 11 patients were diagnosed as having acquired anovestibular fistula with normal anal opening and were managed by conservative management. Results: Most of them presented with diarrhea and labial redness. One patient was considered to have fistula of congenital origin and was managed surgically. Eleven patients presented between the ages of 1.5-11 months and were considered as cases of acquired anovestibular fistula and only two of them required surgical management in the form of colostomy and fistula excision. Others were successfully managed by conservative treatment; the fistulous output and labial redness decreased gradually within a period of 5-19 (average 11.5) days. Conclusions: Not all presentations of anovestibular fistula with normal anal opening can be considered as congenital. Presence of inflammation, paramedian fistula, and a favourable response to conservative management/colostomy suggest acquired etiology. Trial of conservative management should be given in the acquired variety.